Detection and Genetic Characterization of Viruses Present in Free-Ranging Snow Leopards Using Next-Generation Sequencing - Johansson, Örjan; Ullman, Karin; Lkhagvajav, Purevjav; Wiseman, Marc; Malmsten, Jonas; Leijon, Mikael (Frontiers in Veterinary Science, 2020)
Snow leopards inhabit the cold, arid environments of the high mountains of South and Central Asia. These living conditions likely affect the abundance and composition of microbes with the capacity to infect these animals. It is important to investigate the microbes that snow leopards are exposed to detect infectious disease threats and define a baseline for future changes that may impact the health of this endangered felid. In this work next-generation sequencing is used to investigate the fecal (and in a few cases sera) virome of seven snow leopards from the Tost mountains of Mongolia. The viral species to which the greatest number of sequences reads showed high similarity was rotavirus. Excluding one animal with overall very few sequence reads four of six animals (67%) displayed evidence of rotavirus infection. A serum sample of a male and a rectal swab of a female snow leopard produced sequence reads identical to felid herpesvirus 1, providing the first evidence that this virus infects snow leopards. In addition, the rectal swab from the same female also displayed sequence reads most similar to feline papillomavirus 2, which is the first evidence for this virus infecting snow leopards. The rectal swabs from all animals also showed evidence for the presence of small circular DNA viruses, predominately CRESS viruses and in one case feline anellovirus. Several of the viruses implicated in the present study could affect the health of snow leopards. In animals which are under environmental stress, for example young dispersing individuals and lactating females, health issues may be exacerbated by latent virus infections. It is therefore important to continue to monitor the evolution of the virome of snow leopard populations to know when supportive countermeasures might be needed.